Large-Scale Convergence of Receptor Cell Arrays Onto Afferent Terminal Arbors in the Lorenzinian Electroreceptors of Polyodon - Russell, David F.; Warnock, Thomas C.; Zhang, Wenjuan; Rogers, Desmon E.; Neiman, Lilia L. (Frontiers in Neuroanatomy, 2020)
Certain sensory receptors contain many transducers, converging onto few afferents. Convergence creates star-topology neural networks, of iterative parallel organization, that may yield special functional properties. We quantitated large-scale convergence in electroreceptors on the rostrum of preadult paddlefish Polyodon spathula, a cartilaginous Acipenseriforme vertebrate, and analyzed the afferent terminal branching underlying the convergence. From neurophysiological mapping, a recorded afferent innervated 23.3 ±9.1 (range 6-45) ampullary organs, and innervated every ampullary organ within the receptive field’s sharp boundary. Ampullary organs each contained ~705 Lorenzinian receptor cells, from imaging and modeling. We imaged 3 serial types of afferent branching at electroreceptors, after immunofluorescent labeling for neurite filaments, glial sheaths, or nodal ion channels, or by DiI tracing. (i) Myelinated tree: Each of 3.08 ±0.51 (2-4) parallel afferents from a cranial nerve (ALLn) entered a receptive field from deeper tissue, then branched into a laminar tree of large myelinated dendrites, parallel to the skin, that branched radially until ~9 extremities with heminodes. The extremities were candidate sites of spike encoders. (ii) Inline transition: Heminodes led distally into local unmyelinated (MBP-) arbors, originating at inline branching structures, covered by terminal (satellite) glia exhibiting calbindin+ and NMDAR1+ immunoreactivity. These transition zones included globular structures, 4-6 microns wide, from which multiple submicron neurites erupted, a possibly novel type of neuronal branching. The fine parallel neurites formed loose fascicles projecting ~105 microns distally to co innervate local groups of 2.62 ±0.77 (1-4) adjacent ampullary organs. (iii) Radial arbors: Receptor cells in the electrosensory neuroepithelium covering the basal pole of each ampullary organ were innervated by bouton endings of radial neurites, unmyelinated and submicron, forming a thin curviplanar lamina distal to the WGA+ basal lamina. The profuse radial neurites diverged from thicker (~2 micron) basal trunks. Overall, an average Polyodon electroreceptor formed a star topology array of ~9 sensor groups. Total convergence ratios were ~16426 ±6415 parallel receptor cells per afferent per mean receptive field, assuming 100% innervation. Large-scale convergence likely increases the signal-to-noise ratio (SNR) of stimulus encoding into spiking afferent output, increasing receiver sensitivity. Unmyelinated arbors may also regenerate and repair the afferent innervation of ampullary organs.